MODERN APPROACHES TO THE TREATMENT OF PURULENT WOUNDS OF THE BOTTOM OF THE ORAL CAVITY AND NECK WITH THE USE OF BLUE LIGHT AND BACTERIOPHAGES - Yeshiev Abdyrakman Moldalievich; Azimbaev Nurlanbek Mukhtaralievich; Moldaliev Zhoomart Tumakovich (World Science, 2024)
The most common oral diseases are: dental caries and periodontitis. The low level of prevention and untimely detection of diseases lead to the development of complications (periostitis, abscess, phlegmon, etc.). The problem of purulent infection in the maxillofacial area, as a section of general surgery, is equally relevant at the present stage and also does not show a tendency to decrease. The purpose of the study was to study the effectiveness of treating purulent wounds with blue light irradiation in combination with a bacteriophage. The material for the study was 100 people with phlegmon of the floor of the mouth and neck, who were treated in the Department of Maxillofacial Surgery of the Osh Interregional United Clinical Hospital. To carry out etiotropic antibiotic therapy, the quantitative and qualitative composition of the microbial flora has been studied. All patients with phlegmon of the bottom of the mouth and neck were drained according to our method “Method of opening phlegmon of the bottom of the mouth and neck with a “U” shaped incision (Patent of the KR No. 1876).” It has been established that complex treatment using blue light and bacteriophage has a positive effect on a purulent wound from the first hours. The main feature of the wound process in the treatment of purulent wounds using blue light with a wavelength of 450 nm and bacteriophage is accelerated wound healing, rapid maturation of fibroblasts in granulation tissue, active formation of collagen fibers and a less pronounced inflammatory reaction. Results of morphological studies: an increase in the phagocytic activity of neutrophils, activation of the proliferation of cellular elements of the macrophage and fibroblastic series, angio and collagenogenesis, accelerated maturation and fibrosis of granulation tissue were established. Microbiological studies have shown a decrease in bacterial contamination of wound tissues compared to traditional treatment.